Strain Engineering and Halogen Compensation of Buried Interface in Polycrystalline Halide Perovskites - Zhou, Bin; Shang, Chuanzhen; Wang, Chenyun; Qu, Duo; Qiao, Jingyuan; Zhang, Xinyue; Zhao, Wenying; Han, Ruilin; Dong, Shuxin; Xue, Yuhe; Ke, You; Ye, Fengjun; et al. (Research (Washington), 2024)
Inverted perovskite solar cells based on weakly polarized hole-transporting layers suffer from the problem of polarity mismatch with the perovskite precursor solution, resulting in a nonideal wetting surface. In addition to the bottom-up growth of the polycrystalline halide perovskite, this will inevitably worse the effects of residual strain and heterogeneity at the buried interface on the interfacial carrier transport and localized compositional deficiency. Here, we propose a multifunctional hybrid pre-embedding strategy to improve substrate wettability and address unfavorable strain and heterogeneities. By exposing the buried interface, it was found that the residual strain of the perovskite films was markedly reduced because of the presence of organic polyelectrolyte and imidazolium salt, which not only realized the halogen compensation and the coordination of Pb 2+ but also the buried interface morphology and defect recombination that were well regulated. Benefitting from the above advantages, the power conversion efficiency of the targeted inverted devices with a bandgap of 1.62 eV was 21.93% and outstanding intrinsic stability. In addition, this coembedding strategy can be extended to devices with a bandgap of 1.55 eV, and the champion device achieved a power conversion efficiency of 23.74%. In addition, the optimized perovskite solar cells retained 91% of their initial efficiency (960 h) when exposed to an ambient relative humidity of 20%, with a T80 of 680 h under heating aging at 65 °C, exhibiting elevated durability.